REPRESENTASI KESANTUNAN POSITIF-NEGATIF BROWN DAN LEVINSON DALAM WACANA DIALOG DI TELEVISI - Pramujiono, Agung (BAHASTRA, 2015)
The research aimed at describing Brown and Levinson;s language politeness strategies in dialogoues discourse on television. It focused on (1) the used of positive language politeness strategies and (2) the used of negative language politeness strategies in dialogoues discourse on television. This research was approached qualitatively using etnoghrapy of communication design. The data concisted of two kinds, they were the utterances data and field notes. They were recorded from the interactive dialogs on three television stations, i.e. tvOne, MetroTv, and TVRI. The collected data were analyzed using interactive models Miles and Huberman. Based on the data analysis, some findings were made as follows: In the dialoguous discourse on television, the positive politeness strategies used by the interactants covered (1) the uses of emphaty and symphaty, (2) the uses of group identity markers, (3) the uses of asking for agreement, (4) the uses of repetition of utterances, (5) the uses of humor, (6) the uses of being optimistic, (7) the uses of offers and promises, (8) involving the hearer and the speaker in the activities, (9) seeking for reasons or giving questions, and (10) extending presents. Related to the uses of negative politeness strategies used by the interactants covered (1) the uses of indirect utterances , (2) asking for apologies, (3) the uses of impersonal form, (4) the uses of general rules of interaction, and (5) the uses of respect.